The complete mitochondrial genome of the snapping shrimp, Alpheus brevicristatus De Haan, 1844 (Crustacea, Decapoda, Alpheidae) - Yan-Bin Yang; Fang-Chao Zhu; Xin Liu; Lin-Tao Zhao; Shuo Yu; Xu-Yang Chen (Mitochondrial DNA. Part B. Resources)
The snapping shrimp Alpheus is the genus with most species in the Alpheidae family. In this study, the mitochondrial genome of Alpheus brevicristatus De Haan, 1844 has been sequenced and analyzed. The circular mitogenome was 15,705 bp in length with an A+T content of 62.64%. It contained 37 genes typically found in metazoans, and one non-coding region. Phylogenetic analysis highly supported the placement of A. brevicristatus within Alpheidae. This study provides important mitochondrial genome data that could be used for further phylogenetic and evolutionary study of caridean snapping shrimps.